Entrepreneurial Intention on Studentpreneurs to become Entrepreneur - Manik, Ester; Sidharta, Iwan (International Review of Management and Marketing, 2016)
An increase in number of entrepreneurs is one important factor for the economic security of a country. The role of universities in preparing entrepreneurs is proven for contributing the national economy. Thus there is a need for a study to determine the factors that influence students to choose a career as an entrepreneur when they graduate. This study aims to determine the factors that influence the intention of students to become entrepreneurs. Exploratory research methods with data analysis techniques using Structural Equation Modelling (SEM), component-based Partial Least Squares (PLS). The number of respondents as many as 241 students with the data collection technique accidental sampling. The results showed that the effect of economic opportunity and challenge, perceived confidence, security and work load, self-efficacy and facilitating condition significantly influence the intention of students to become entrepreneurs. As for the influence of the entrepreneurial intention of 43.3%. Thus, the need for attention by the university to improve the quality of students to become a reliable and useful entrepreneurs in order to form national economic resilience. Keywords: economic opportunity, perceived confidence, security, self efficacy, facilitating condition, entrepreneurial intention JEL Classifications: L26, M13